2015
DOI: 10.1074/jbc.m114.606608
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptors

Abstract: Background: C. elegans encodes three metabotropic glutamate receptors: mgl-1, mgl-2, and mgl-3. Results: mgl-1 and mgl-3, but not mgl-2, modulate activity in the neural circuit underlying feeding behavior. Conclusion: mgl-1 is the major contributor to the inhibitory tone of the feeding circuit and context-dependent feeding behavior. Significance: C. elegans provides a model for systems-level understanding of metabotropic glutamate receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…There is also evidence that the metabotropic glutamate receptor, MGL-1, plays a role in feeding behaviour following acute removal of food in C. elegans (Dillon et al 2015). Following acute removal of food, mgl-1 mutants pump at a raised rate compared to N2, indicating that activation of MGL-1 (which is widely expressed in the extrapharyngeal and pharyngeal nervous system including NSM) leads to inhibition of pharyngeal pumping.…”
Section: Glutamate and Pharyngealmentioning
confidence: 99%
“…There is also evidence that the metabotropic glutamate receptor, MGL-1, plays a role in feeding behaviour following acute removal of food in C. elegans (Dillon et al 2015). Following acute removal of food, mgl-1 mutants pump at a raised rate compared to N2, indicating that activation of MGL-1 (which is widely expressed in the extrapharyngeal and pharyngeal nervous system including NSM) leads to inhibition of pharyngeal pumping.…”
Section: Glutamate and Pharyngealmentioning
confidence: 99%
“…These results showed how degenerate neural pathways, in which multiple elements can perform the same function, regulate behaviour in a simple model system. Dillon et al [96] used ChR2-mediated excitation of glutamatergic pharyngeal neurons to investigate the function of metabotropic glutamate receptors (mGluRs). The authors found that glutamate receptors are required for presynaptic modulation of pharyngeal behaviour and electrical activity.…”
Section: Pharyngeal Neuronsmentioning
confidence: 99%
“…The Caenorhabditis elegans genome encodes three metabotropic glutamate receptors, named MGL-1, MGL-2 and MGL-3. Sequence analysis suggests the three receptors each representing orthologues of one of the mammalian mGluR subfamilies, and the functional diversity within the mammalian family is conserved in C. elegans (Dillon et al 2015). There is currently a limited understanding of this class of receptor, compared to the ionotropic families of glutamate receptors (viz NMDA, AMPA and Ivermectin channels) in C. elegans.…”
Section: Introductionmentioning
confidence: 99%
“…We have probed its function using the mGluR agonist L-CCG-I to show that it is a negative regulator of pharyngeal network activity. MGL-1 is required for coordinating plasticity in feeding behaviour and reproduction upon the removal of food (Dillon et al 2015;Jeong and Paik 2017). To build upon this, we have identified candidate MGL scaffolding proteins and screened for their potential to modulate the activity of the pharyngeal network.…”
Section: Introductionmentioning
confidence: 99%